Extracellular Polymeric Substances in Textile Industry - Topal, Murat; Arslan Topal, E. Işıl (Springer International Publishing, 2022)
Different microorganisms secrete extracellular polymeric substances that are also known as exopolymeric substances, exopolymers, extracellular polysaccharides, and exopolysaccharides. Extracellular polymeric substances that protect the microorganisms from the environmental stresses are mainly composed of lipids, proteins, polysaccharides, and nucleic acids. They have unique characteristics with functional properties such as addhesion, binding activity, water retention, sorption and so on. The extracellular polymeric substances are valuable products because of their various applications in different industries about textile, pharmaceutical, food, agriculture, cosmetic, and environment. The extracellular polymeric substances are valuable for textile industry as being sustainable resource as well as environmental friendly properties. In this chapter, we have evaluated extracellular polymeric substances followed by the main functions and applications of the extracellular polymeric substances. Moreover, we have emphasized the applications for various extracellular polymeric substances in textile. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.
Keywords: Alginate; Cellulose; Chitosan; Pullulan; Xanthan